60th ANNIVERSARY OF THE BUDKER INSTITUTE OF NUCLEAR PHYSICS (BINP), SB RAS. 100th ANNIVERSARY OF THE BIRTH OF G I BUDKER : Multiple-mirror trap: a path from Budker magnetic mirrors to linear fusion reactor. (7th September 2018) - Burdakov, A V; Postupaev, V V
Abstract: This review is focused on multiple-mirror traps for high-temperature plasma confinement that were proposed by Budker, Mirnov, and Ryutov and independently by Logan, Lichtenberg, and Lieberman in the early 1970s. The proposed magnetic system solved problems with the kinetic instabilities of classical open traps and significantly increased the plasma lifetime. We review the history of this field and discuss its achievements and prospects.